Quantum mechanical calculation of electron spin - Zhao Hai-Long (Open Physics, 2017)
The classical and quantum mechanical methods are used respectively to calculate the electron spin. It is shown that the classical method cannot derive the correct magnetic moment value. Assuming that the rest energy of the electron originates from the kinetic energy of the virtual particles, the electron spin motion equation and spin wave function can be derived. In the case of the quantum numbers of spin angular momentum and magnetic moment being 1/2 and 1 respectively, their correct values can be obtained. In the meanwhile, the anomalous magnetic moment is evaluated based on the wave function of the spinning electron. Suppose the probability of virtual photons converting into electron-positron pairs to be 0.00141, the result agrees with that of quantum electrodynamics. Given that the energy of the virtual photon obeys the classical Maxwell-Boltzmann distribution, the self-energy of the electron will be finite. In addition, the hierarchy problem can be solved with the same hypothesis.